2017
DOI: 10.1177/0898756417705229
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Force Direction on the Fracture Pattern and Fracture Resistance of Canine Teeth in Dogs

Abstract: Biomechanical studies of the elongated canine tooth of animals are few, and thus our understanding of mechanical and physical properties of animal teeth is limited. The objective of the present study was to evaluate the influence of force direction on fracture resistance and fracture pattern of canine teeth in an ex vivo dog cadaver model. Forty-five extracted canine teeth from laboratory beagle dogs were standardized by hard tissue volume and randomly distributed among 3 force direction groups. The teeth were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
6
1
Order By: Relevance
“…However, previous studies have found no detectable effect of freezing, or storage temperature in general, on the behavior of human periodontal ligaments or fracture resistance when tooth strength is evaluated by a force displacement curve (32,33). Furthermore, the storage and harvesting methods used in this study were consistent with previously reported methods in canines (22,26,27). Based on this information, the authors believe it was unlikely that storage conditions had a significant effect on the results of the present study, as all teeth were stored and tested in the same manner.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, previous studies have found no detectable effect of freezing, or storage temperature in general, on the behavior of human periodontal ligaments or fracture resistance when tooth strength is evaluated by a force displacement curve (32,33). Furthermore, the storage and harvesting methods used in this study were consistent with previously reported methods in canines (22,26,27). Based on this information, the authors believe it was unlikely that storage conditions had a significant effect on the results of the present study, as all teeth were stored and tested in the same manner.…”
Section: Discussionsupporting
confidence: 88%
“…For reference, the difference between the crown height to diameter ratio in the Soltero-Rivera Paper (23) was 2.38 standard deviation lower than our mean, and so we would predict an average difference of 33 N (95%CI: −288, 221) in force to fracture between the two study cohorts based on differences in crown height to diameter ratio alone. Thus, our study is not in conflict with the findings of numerous other biomechanical studies (23,26,27) that found there is a trend for decreased fracture resistance as the height to diameter ratio increased. Overall, the authors believe the lack of identified statistical significance was primarily due to the minimal variation in crown height to diameter ratio in the cohort, as was intentional in the study design, rather than the height to diameter ratio not being a significant contributor to overall fracture resistance in endodontically treated maxillary fourth premolar teeth.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This type of work has been undertaken on domestic dog ( Canis familiarus ) canines, with patterns observed that support some of the above predictions [ 28 , 81 ]. For example, a trend toward lower force to fracture (N) when teeth are loaded in the lingual–labial direction [ 81 ], in addition to transverse fracture being one of the most common fracture types under lingual–labial loading [ 81 ]. Future research should expand on these studies by including a broader range of canine forms.…”
Section: Discussionmentioning
confidence: 99%
“…However, this requires further study and validation through closer inspection of specimens with broken teeth to identify the type and location of breakage, in addition to in vivo breakage testing of real teeth under controlled conditions. This type of work has been undertaken on domestic dog ( Canis familiarus ) canines, with patterns observed that support some of the above predictions [28,81]. For example, a trend toward lower force to fracture (N) when teeth are loaded in the lingual–labial direction [81], in addition to transverse fracture being one of the most common fracture types under lingual–labial loading [81].…”
Section: Discussionmentioning
confidence: 99%